Fuzzy nation [compact disc, unabridged] - Scalzi, John, 1969- (Brilliance Audio on compact disc., 2011)
Jack Holloway works alone. Hundreds of miles from ZaraCorp's headquarters on planet, 178 light-years from the corporation's headquarters on Earth, Jack is content as an independent contractor. As for his past, that's not up for discussion. Then, in the wake of an accidental cliff collapse, Jack discovers a seam of unimaginably valuable jewels, to which he manages to lay legal claim just as ZaraCorp is cancelling their contract with him for his part in causing the collapse.